THE FOREIGN EXPERIENCE OF THE DEVELOPMENT OF TRANSPORT SERVICES IN THE CONTEXT OF THE DIGITALIZATION OF THE ECONOMY (World Bulletin of Management and Law, 2025)
In the era of rapid digital transformation, the transport services sector is undergoing profound changes across the globe. This article explores foreign experiences and best practices in the development of transport services in the context of the digitalization of the economy. By analyzing case studies from technologically advanced countries, the paper highlights the integration of digital tools such as intelligent transport systems (ITS), real-time data analytics, automation, and AI-based logistics management. It also examines the regulatory frameworks, public-private partnerships, and innovation policies that facilitate digital innovation in the transport industry. The findings offer valuable insights for policymakers and industry stakeholders seeking to modernize transport services in emerging economies through digital solutions.
Keywords: Digitalization; transport services; international experience; intelligent transport systems